DINAMIKA MAKNA CINTA DALAM LAGU POPULER INDONESIA TAHUN 2023–2024: KAJIAN SEMANTIK - Novita Fitri Astuti (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study aims to describe the denotative and connotative meanings in three popular Indonesian songs, namely "Lesung Pipi" by Raim Laode, "Penjaga Hati" by Nadhif Basalamah, and "Kupu-Kupu" by Tiara Andini, and explain their relevance to Indonesian language learning in the argumentative text material in the sub-chapter of listening and finding song messages at the junior high school level. This study uses a qualitative descriptive method with a semantic approach. The research data are song lyrics that are selected purposively based on their popularity, depth of meaning, and their closeness to the lives of teenagers. The analysis is carried out by identifying the elements of denotative and connotative meaning in each lyric, then interpreting the moral messages and values ​​contained therein. The results show that the three songs have a tendency towards the theme of admiring in silence, which is expressed through poetic diction, natural symbols, and metaphors. The denotative meaning in the lyrics describes concrete events, while the connotative meaning strengthens the emotional message and moral values ​​such as sincerity, patience, and loyalty. These findings have significant pedagogical relevance, as semantic analysis of popular songs can be utilized as a contextual, engaging, and meaningful learning strategy to train students' critical thinking skills and language appreciation in understanding song messages in accordance with the principles of the Independent Curriculum.